2021
DOI: 10.1071/py20209
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of human papillomavirus self-sampling into the revised National Cervical Screening Program: a qualitative study of GP experiences and attitudes in rural New South Wales

Abstract: Human papillomavirus self-sampling is part of the revised Australian National Cervical Screening Program for eligible under- or never-screened women. Although research demonstrates self-sampling as an acceptable method from the perspective of women, little is known about GP experiences and perspectives of this new screening alternative. This study sought to explore the experiences and perspectives of rural GPs towards the revised National Cervical Screening Program and the new self-sampling option. Semistructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…Very limited promotion regarding the availability of self-collection to both consumers and health care providers has very likely contributed to a substantially low adoption of restricted self-collection in the first two years of the renewed program [ 33 ]. Among primary care practitioners, there appears to be the strong misconception that self-collection is inferior compared to a clinician-collected HPV samples [ 27 , 31 , 34 ] with similar findings have been documented elsewhere [ 28 , 29 , 32 ]. At the time of the policy decision in Australia (in around 2014), the early evidence suggested that, while HPV testing on a self-collected sample had a greater sensitivity than Pap testing, it was slightly inferior to HPV testing on a clinician-collected sample, because many of the studies had used HPV tests based on signal-amplification assays rather than PCR-based assays [ 35 ].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Very limited promotion regarding the availability of self-collection to both consumers and health care providers has very likely contributed to a substantially low adoption of restricted self-collection in the first two years of the renewed program [ 33 ]. Among primary care practitioners, there appears to be the strong misconception that self-collection is inferior compared to a clinician-collected HPV samples [ 27 , 31 , 34 ] with similar findings have been documented elsewhere [ 28 , 29 , 32 ]. At the time of the policy decision in Australia (in around 2014), the early evidence suggested that, while HPV testing on a self-collected sample had a greater sensitivity than Pap testing, it was slightly inferior to HPV testing on a clinician-collected sample, because many of the studies had used HPV tests based on signal-amplification assays rather than PCR-based assays [ 35 ].…”
Section: Discussionmentioning
confidence: 64%
“…The National Cancer Screening Register now has a healthcare provider portal with integration with some commonly used practice management software, which may overcome this sort of issue in future (and it is now less of a barrier as there is universal access to self-collection). It is important that the system level issues reported by our study and elsewhere, which may have contributed to a general confusion and mistrust of self-collection [ 27 , 31 , 32 ] are successfully addressed and practitioner attitudes changed moving forward.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…46 Evidence suggests that healthcare professionals consider self-collection as a valuable option, particularly for under-and never-screened women, but they remain uncertain and hesitant about its efficacy and continue to view clinician-collected samples as the gold standard. 25,[46][47][48] Despite it being highly anticipated, there were delays to the introduction of selfcollection. This was largely due to the need for laboratories to conduct and have approved their own in-house validation to process self-collected samples; only one laboratory had done so in Australia when self-collection was introduced.…”
Section: Discussionmentioning
confidence: 99%
“…It highlights the need to ensure that clinicians are aware of self‐collection and are confident in recommending it to their clientele 46 . Evidence suggests that healthcare professionals consider self‐collection as a valuable option, particularly for under‐ and never‐screened women, but they remain uncertain and hesitant about its efficacy and continue to view clinician‐collected samples as the gold standard 25,46-48 …”
Section: Discussionmentioning
confidence: 99%